The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40121-020-00384-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Focused Selection of PrEP Medication for Individuals at Risk of HIV: A Narrative Review

Abstract: Pre-exposure prophylaxis (PrEP) medication is a key component of the HIV prevention strategy in the US, which has been demonstrated to be highly effective in preventing HIV acquisition among individuals at risk. Two PrEP medications are currently approved: emtricitabine/ tenofovir disoproxil fumarate (Truvada Ò ; F/TDF) was approved by the US Food and Drug Administration in 2012, followed by emtricitabine/tenofovir alafenamide (Descovy Ò ; F/TAF) in 2019. An ongoing randomized, double-blind, Phase 3 study (DIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 89 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…Some clinicians recommended to prescribe upgraded ART drugs to eliminate the potential risks ( 34 36 ). Also the updated guidelines for PrEP in the United States recommended the use of updated PrEP drugs (emtricitabine/tenofovir alafenamide [Descovy ® F/TAF]) ( 37 ) because of its less side effect on bone and good efficacy ( 38 ). However, these updated drugs were more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinicians recommended to prescribe upgraded ART drugs to eliminate the potential risks ( 34 36 ). Also the updated guidelines for PrEP in the United States recommended the use of updated PrEP drugs (emtricitabine/tenofovir alafenamide [Descovy ® F/TAF]) ( 37 ) because of its less side effect on bone and good efficacy ( 38 ). However, these updated drugs were more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…An age-associated decline in glomerular filtration rate (GFR) is observed in longitudinal and cross-sectional studies [ 59 , 60 ]. Some populations are at an increased risk of accelerated kidney dysfunction due to concomitant medications [ 61 – 63 ], lifestyle (e.g., tobacco use, alcohol, and illicit substance use disorders) [ 64 – 66 ], comorbidities (e.g., hypertension, diabetes, established cardiovascular disease, as well as and family history) [ 61 ]. The presence of albuminuria, even with preserved estimated GFR (eGFR), is meaningful as it is known to increase the progression of renal disease.…”
Section: Renal Considerations and Supporting Evidencementioning
confidence: 99%
“…These effects of PrEP on BMD are important, even in a younger population that may easily recover from fracture events because many individuals remain on PrEP for many years. Once peak BMD is established, typically by 30 years of age [ 61 ], it slowly declines throughout the remainder of the lifespan [ 82 ]. In individuals who are on PrEP between the ages of 20 and 30 years old, the medication may reduce bone accretion leading to a lower peak bone mass.…”
Section: Bone Considerations and Supporting Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…An ever-growing epidemic of syphilis has been reported mainly among men who have sex with men (MSM), which is driven by online social networking, condomless sex, group sex, and recreational drug use [ 2 ]. Individuals receiving biomedical HIV treatment and prevention are particularly at high risk for syphilis [ 3 , 4 ]. The surveillance data from the USA showed that primary and secondary syphilis were more prevalent among HIV-positive MSM (7.0%) than among HIV-negative MSM (3.4%) in 2018 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%